2015
DOI: 10.1530/joe-15-0139
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced obesity causes peripheral and central ghrelin resistance by promoting inflammation

Abstract: Ghrelin, a stomach-derived orexigenic peptide, transmits starvation signals to the hypothalamus via the vagus afferent nerve. Peripheral administration of ghrelin does not induce food intake in high fat diet (HFD)-induced obese mice. We investigated whether this ghrelin resistance was caused by dysfunction of the vagus afferent pathway. Administration (s.c.) of ghrelin did not induce food intake, suppression of oxygen consumption, electrical activity of the vagal afferent nerve, phosphorylation of ERK2 and AMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 45 publications
5
85
1
Order By: Relevance
“…In a recent study, we showed that 12-week HFD feeding (60% of calories as fat) induced accumulation and activation of M1 (Iba1 + /CD86 + ) macrophages both in the nodose ganglion and hypothalamus of mice [18]. In the one-day HFD study described here we observed elevated recruitment of M1 macrophages in the nodose ganglion but not in the hypothalamus, suggesting that the nodose ganglion receives inflammatory signals before the hypothalamus.…”
Section: Discussionsupporting
confidence: 50%
“…In a recent study, we showed that 12-week HFD feeding (60% of calories as fat) induced accumulation and activation of M1 (Iba1 + /CD86 + ) macrophages both in the nodose ganglion and hypothalamus of mice [18]. In the one-day HFD study described here we observed elevated recruitment of M1 macrophages in the nodose ganglion but not in the hypothalamus, suggesting that the nodose ganglion receives inflammatory signals before the hypothalamus.…”
Section: Discussionsupporting
confidence: 50%
“…DIO also attenuates fasting-induced hyperphagia by suppressing arcuate neuronal activation and hypothalamic NPY/AgRP mRNA expression [16], showing that DIO affects other physiological cues designed to maintain energy homeostasis. The effects of DIO on ghrelin resistance are not limited to food intake, as ghrelin fails to reduce oxygen consumption in HFD-fed mice relative to chow-fed mice [58]. …”
Section: Positive Energy Balance and Ghrelin Resistancementioning
confidence: 99%
“…These deficits occur after several weeks of HFD feeding (Briggs et al, 2014), and persist while body weight remains high, but can be reversed with dietinduced weight loss (Briggs et al, 2013). Others have recently demonstrated ghrelin resistance in the vagal afferents and nodose ganglion, suggesting that this phenomenon is not limited to the hypothalamus (Naznin et al, 2015). The interaction between HFD feeding and reward processing is as yet not well understood, however ghrelin resistance appears to extend to behavioural measures beyond feeding.…”
Section: Introductionmentioning
confidence: 99%